Performance of thin film nanocomposite membranes incorporated with zwitterion and titania nanotube for pressure retarded osmosis - Sharudin, Syafiq Izzany (2020)
Osmotic power generation through pressure retarded osmosis (PRO) has been recognized as an alternative source of energy. Membrane is one of the major elements to guarantee the successful application of PRO for power generation. However, the major current limitation in PRO lies in the design of a high-performance membrane which is endowed with desired properties in terms of flux and anti-fouling properties. Hence, the main objective of this study was to fabricate a hydrophilic and high flux PRO thin film nanocomposite (TFN) membrane with high flux and anti-fouling properties through the incorporation of zwitterionic polymers, poly (3- methacryloylethoxy carbonyl pyridinium sulfopropyl betaine) (PMAPS) in the substrate and titanium dioxide nanotube (TNT) into the polyamide (PA) layer. Different loadings of PMAPS were physically mixed with polysulfone (PSF) dope prior to the formation of the TFC substrate. Further optimization via etching treatment was performed to increase substrate porosity and the PA selective layer incorporated with TNT was formed on top of the substrate through interfacial polymerization technique. Membrane characterizations were carried out using scanning electron microscope, transmission electron microscopy, Fourier-transform infrared spectroscopy, x-ray diffractometer, energy dispersive x-ray, and contact angle goniometer. The water flux and power density performance of the zwitterion incorporated TFN membranes were evaluated using a custom-made PRO system. The power density exhibited by etched TFN membrane incorporated with 2.0% PMAPS (PSF/PMAPS-2.0 Etched TFN) was 2.12 W/m2 at 5 bar while unetched TFN membrane exhibited power density of 0.96 W/m2 at 7 bar. Addition of TNT resulted in the highest power density of 2.22 W/m2 at 5 bar. In terms of anti-fouling properties, PSF/PMAPS-2.0 Etched TFN achieved higher normalized water flux with 97% flux recovery compared to control substrate with 90% flux recovery. In conclusion, membrane modification using PMAPS zwitterions and TNT nanoparticles improved water flux, anti-fouling properties and power density.